Progesterone Serum Level in-Labor Women does not Differ with not in-Labor Women - Hutomo, Caroline (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objectives: To find out the relation of serum progesterone level between patients in-labor and pregnant patients not in-labor. Methods: This was an analytic cross-sectional study, comparing serum progesterone level between in-labor gravida and not in-labor gravida. Subjects were in-labor gravida (n=21) and not in-labor gravida (n=24) admitted to Sanglah Hospital from April to August 2011. The data were analyzed by SPSS 16.0. Independent sample ttest and Fisherâs exact test were used. Results: Mean serum progesterone level were 214.90Â±92.06 inlabor gravida and 190.69Â±76.02 not in-labor gravida (t = 0.966 and p = 0.399). Conclusions: There is no difference in serum progesterone level between in-labor and not in-labor pregnant women. [Indones J Obstet Gynecol 2012; 36-4: 185-7] Keywords: labor, progesterone, progesterone withdrawal